Physical Condition Survey of Futsal Extracurricular Students at Smp Negeri 31 Bengkulu Utara - Pebriana, Yegga; Suwarni, Suwarni; Martiani, Martiani (Journal of Education, 2025)
This study aims to determine the condition of Futsal players at SMPN 31 North Bengkulu. Research is quantitative descriptive research. The method used is survey research with a quantitative descriptive approach with data collection techniques using shooting test instruments. The subjects of this research were all students of SMPN 31 North Bengkulu, totaling 22 students. The analysis technique used is descriptive statistics by pouring the frequency into percentage form. The results of this study indicate that the results of the endurance test of SMPN 31 North Bengkulu futsal players using the bleep test measuring instrument with an average value of 32.53 (ml / kg.BB / min) are in the medium category. push ups with an average value of 19 are in the medium category. 50 meter sprint with an average value of 7.33 seconds is in the deficient category. zig-zag run test with an average value of 7.98 seconds is in the deficient category. flexiometer test with an average value of 18.5 cm is in the good category. standing stork test tool with an average value of 31 seconds is in the medium average category. The conclusion is that the category is Moderate.